1993
DOI: 10.2307/4088632
|View full text |Cite
|
Sign up to set email alerts
|

Nest-Site Characteristics and Nest Predation in Harris' Sparrows and White-Crowned Sparrows in the Northwest Territories, Canada

Abstract: ABssAcr.-I examined the relationship of nest-site and nest-patch characteristics to nest success in ground-nesting Harris' Sparrows (Zonotrichia querula) and Gambel's White-crowned Sparrows (Z. leucophrys gambelii) in the forest-tundra ecotone of the Northwest Territories, Canada. I found 34% of all Harris' Sparrow nests depredated, primarily by arctic ground squirrels (Spermophilus parryii), while no White-crowned Sparrow nests were disturbed by predators. White-crowned Sparrow nests appeared to be less susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 30 publications
0
36
0
2
Order By: Relevance
“…Many researchers have noted relationships between vegetation structure and/or floristics and nest site selection by forest-dwelling passerine birds (Martin and Roper 1988;Sakai and Noon 1991;Knopf and Sedgewick 1992;Kelly 1993;Norment 1993). The influence of vegetative characteristics on nest site selection 15 may be exerted on several scales.…”
Section: Literature Review and Conceptual Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have noted relationships between vegetation structure and/or floristics and nest site selection by forest-dwelling passerine birds (Martin and Roper 1988;Sakai and Noon 1991;Knopf and Sedgewick 1992;Kelly 1993;Norment 1993). The influence of vegetative characteristics on nest site selection 15 may be exerted on several scales.…”
Section: Literature Review and Conceptual Developmentmentioning
confidence: 99%
“…Several factors may affect selection of a nest site or patch characterized by particular vegetative structure or floristics. Martin and Roper (1988) and Norment (1993) found that nest placement by hermit thrushes (Catharus guttatus) within a plant and within a patch affected probabili^ of nest predation. In both studies, nests placed in denser vegetation were less likely to be depredated.…”
Section: Literature Review and Conceptual Developmentmentioning
confidence: 99%
“…Recently, nest orientation has also been shown to vary intraspecifically, in a predictable manner, with latitude (Burton 2007). Most species, however, show a preference for one direction, generally that which exposes them to, or protects them from, wind and solar radiation (Ardia et al 2006;Burton 2006;Facemire et al 1990;Mezquida 2004;Norment 1993). The barbtails studied here nest in a cool, dark, humid environment, and rear their young in thick, enclosed nests with a downward-opening entrance tube (Greeney 2008a(Greeney , 2008b.…”
Section: Discussionmentioning
confidence: 98%
“…A wide variety of both circular and linear statistics have been used in previous studies of nest orientation (e.g., Ardia et al 2006;Austin 1974;Burger and Gochfeld 2005;Norment 1993;Ricklefs and Hainsworth 1969). As circular distributions do not usually conform to the assumptions of many of these tests (Cain 1989;Zar 1999), most recent studies of circular data rely on one of several analyses.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation